Innovation management in the company's management system - Ding Lei (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the process of innovation management in banking institutions. The subject of research includes theoretical, methodological, and practical approaches to improving the management of innovative activities in the banking sector. The purpose of the master's thesis is to generalize theoretical and methodological principles and to develop practical recommendations for improving innovation management in banking institutions under modern conditions. Tasks of a qualifying master's thesis include: to reveal the economic essence and significance of innovations in the activities of banking institutions; to generalize the classification of banking innovations and innovative technologies; to investigate models for managing innovative activities within organizations; to provide a general description of JSC "OTP Bank"; to analyze the financial and economic activities of JSC "OTP Bank"; to evaluate the innovative activities of JSC "OTP Bank"; to propose ways to improve and develop innovations and digital technologies in the banking sector; to justify the concept of "green finance" as a tool for the sustainable recovery of Ukraine; to outline the organizational and economic mechanism for financial support of the innovative development of JSC "OTP Bank".
Scientific advisor: Denchik I., PhD in economics, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; company management; innovation activity; company innovation potential; innovation management